Ftr82 is necessary for hair cell morphogenesis and auditory function during zebrafish development. (February 2023) - Yin, Guoli; Qian, Fuping; Yao, Jia; Wang, Ziyang; Wang, Xin; Liu, Dong; Wang, Cheng
Abstract: Damages of sensory hair cells (HCs) are mainly responsible for sensorineural hearing loss, while the pathological mechanism remains not fully understood due to the many potential deafness genes unidentified. f tr82, a member of the largely TRIMs family in fish, has been found specifically expressed in the otic vesicle while its function is still unclear. Here, we investigate the roles of ftr82 in HC development and hearing function utilizing the zebrafish model. The results of in situ hybridization illustrate that ftr82 is always restricted to localize in otic vesicles at different stages. The defects of HCs are observed both in ftr82 morphants and mutants, including significantly decreased crista HCs, shortened cilia as well as remarkably reduced functional HCs in neuromasts, which could be successfully rescued by co-injection of exogenous ftr8 2 mRNA. The behavior assay of startle response indicates that larvae lacking of ftr82 exhibits lower sensitivity to external sound stimuli. Further research reveals that the loss of HCs is mainly caused by cell apoptosis mediated by caspase-3 activation. Our study demonstrates that ftr82 is a crucial hearing-related gene that regulates the HC morphogenesis and auditory function performing, which provides new insight into the rapid identification of the deafness gene.